(untitled) (Research, Society and Development, 2023)
To face the COVID-19 pandemic in-person school activities were interrupted, as a way to provide social isolation and reduce the transmission of the virus. However, drastic and adverse changes can be perceived as potential stressor and, depending on the coping strategies used by the individual to face stressful situations, can cause a greater or lesser level of stress. The objective of the present study consists of a systematic review of the literature that sought to analyze how university students studying health courses have faced the stress triggered by the COVID-19 pandemic. Searches were performed, in August 2021, in CAPES Periodicals and the BVS Regional Portal (Virtual Health Library), grouping the following descriptors: (coping) AND ("college student" OR undergraduate) AND (covid-19 OR COVID OR pandemic). From this search, 199 scientific articles were tracked; however, only 11 articles addressed the strategies used by university students in healthcare courses during a COVID-19 pandemic. The most used strategies by the students were: Social Support, Leisure and Well-Being, Active Coping and Emotional Disengagement. The data from this review can support the development of interventions that can help students to develop effective coping strategies in the prevention and mitigation of stress.